Pengolahan Air Lindi TPA Jabon Griya Mulyo Sidoarjo dengan Metode Constructed Wetland untuk Menyisihkan Parameter COD - Mahendra, Muhammad Bagus Scheva Putra; Amalia, Aussie (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Rapid population growth in Indonesia has led to a significant increase in the volume of waste, which poses a potential threat to the environment. Leachate is a liquid produced when external water infiltrates waste heaps, dissolving both soluble and organic materials through biological decomposition processes. Without proper management, leachate can contaminate water sources and endanger the ecosystem and nearby communities, particularly around the Jabon Landfill (TPA Jabon). One effective method of treating leachate is the use of constructed wetlands, a simple system that uses aquatic plants and microorganisms to reduce pollution. This study evaluates the effectiveness of two aquatic plants, papyrus (Cyperus papyrus) and bulrush (Typha latifolia), in reducing the chemical oxygen demand (COD) of leachate through the constructed wetland system.